The possibilities of diagnosis and treatment of urogenital schistosomatosis in current conditions - F. R. Asfandiyarov; V. Yu. Startsev; A. Yu. Kolmakov (Вестник урологии, 2018)
Introduction. Globalization contributes to the increase in cases of “exotic” bacterial and parasitic infections importation from the countries of the tropical belt to the territory of our country and to European states.Purpose of research. Study and analysis of data on the methods of diagnosis and treatment of urogenital schistosomiasis at the present stageMaterials and methods. The study includes an analysis of the examination and treatment results of 181 patients with urogenital schistosomiasis (US) living in the province of Benguela, Republic of Angola. In 39 (21,5%) cases are revealed schistosomal bladder cancer. All patients with schistosomal bladder cancer (SBC) were operated. 142 patients (78.5%) were divided into two groups. Group I (n = 74) consisted of patients with uncomplicated MS, into group II (n = 68) patients had granulomatous proliferative inflammatory changes in the bladder.Results. Patients with US (n = 142) were examined on an outpatient basis. Cytological exmination of urine sediment (CEUS) showed that eggs of schistosomes were detected in 38 (26.8%) patients. Ultrasound showed specific granulomatous changes in the mucous membrane of the urinary bladder in 28 (19.7%) patients. In 7 (4.9%) cases it showed hydronephrosis, calcification. Bladder wall thickening were detected in 10 (7%) and 99 (69.7%) cases, respectively. Endoscopic examination showed the presence of granulomatous changes in the bladder in 68 (47.9%) patients. Patients of group I (n = 74) received «Praziquantel» in combination with oral antibiotic therapy, which resulted in the relief of macrohematuria and urination disorders. All patients of group II (n = 68) also underwent antibacterial and antiprotozoal therapy. In addition, 35 (24.6%) patients underwent transurethral resection of the bladder (TURB). The results of control observations showed the restoration of bladder mucous layer. Of the 33 (23.2%) patients in Group II who received only antibacterial and antiprotozoal therapy, granulomatous changes persisted in 7 (4.9%) patients. In connection with this, TURB was performed for these patients. Subsequent control studies showed regression of the formations in this group of patientsConclusions. CEUS and ultrasound are not sufficient for diagnosis of US. Cystoscopy is suitable for all patients with MS. It allows to estimate the volume of the bladder lesion, and to determine the indications for performing TURP in addition to the use of antiparasitic and antibacterial therapy.